Rice response to inoculation with P-Solubilizing microorganisms from brazilian cerrado (Bioscience Journal, 2009)
Two experiments were carried out under greenhouse conditions in order to evaluate the rice growth promotion through inoculation of P-solubilizing bacteria and fungi isolated from their rhizoplane plus rhizosphere. The best inoculum concentration was also identified. In both experiments, plants were grown in tubes (330 mL) containing sterilized soil from Cerrado. In the first trial, each plant was inoculated (1 mL with 106 CFU mL-1) of fungi and bacteria isolates and the mixture of both. A completely randomized experimental design with 6 inoculation treatments and 6 replicates was used. In the second trial, plants were inoculated with increasing concentrations (106, 107, 108 and 109 CFU mL-1) with two P-solubilizing bacteria and one P-solubilizing fungi isolates. A completely randomized experimental design, factorial outline 3 x 4 (three P-solubilizing isolates and four increasing inoculum concentration), plus an uninoculated treatment and five replicates were used. In both experiments, plants were harvested 24 days after inoculation with these microorganisms. The height, shoot and root dry matter/length/volume were measured. In the first experiment, the height, root dry matter/length/volume on rice was increased with the inoculation of the P-solubilizing fungi (PSF 8) as well as the mixture of PSF 8 and the P-solubilizing bacteria PSB 24. In the second experiment, PSF 8 also showed the best performance on rice growth promotion mainly at the highest inoculum concentration.